Trilateral retinoblastoma with unilateral eye involvement - Andrade,Gabriel Costa de (2015)
SummaryRetinoblastomas (RB) are the main forms of intraocular tumor in childhood, with a worldwide incidence of 1 case per 15,000 to 20,000 live births. Trilateral RB (RBT) is a rare combination of unilateral or bilateral RB with a midline intracranial neoplasm of neuroblastic origin, usually found in the pineal region or the suprasellar region, presenting variable incidence of 0.5% up to 6% among patients with RB. The article reports a case of unilateral RBT in a patient treated at Hospital A.C.Camargo.